2017
DOI: 10.1021/jacs.6b13149
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Mussel-Inspired Wet Adhesion

Abstract: Nature employs sophisticated control of a structure's properties at multiple length scales to achieve its wet adhesion. However, the translation of such structures has very often been missing in biomimetic adhesives; in turn, their performance is significantly limited as compared to that of biological adhesion, e.g., from mussels. In this Perspective, we overview the major breakthroughs in this field, highlighting the recent advances that demonstrate that holistic multiscale translation is essential to biomime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
281
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 335 publications
(286 citation statements)
references
References 90 publications
0
281
0
Order By: Relevance
“…[9] The commercially available epoxy resins [10] and polyurethanes [11] are reported to demonstrate strong underwater adhesion, but long time of curing is usually required. [15][16][17] The finding of universality of catechol chemistry for wet adhesion has provided a valuable biomimetic source to develop diverse adhesives for use in aqueous environments. [5,12] In addition, electrostatic and hydrophobic interactions were also proved to contribute to enhanced underwater adhesion, but the adhesion strength was relatively poor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The commercially available epoxy resins [10] and polyurethanes [11] are reported to demonstrate strong underwater adhesion, but long time of curing is usually required. [15][16][17] The finding of universality of catechol chemistry for wet adhesion has provided a valuable biomimetic source to develop diverse adhesives for use in aqueous environments. [5,12] In addition, electrostatic and hydrophobic interactions were also proved to contribute to enhanced underwater adhesion, but the adhesion strength was relatively poor.…”
mentioning
confidence: 99%
“…[13,14] In nature, many organisms, such as mussels, barnacles, and castle worms, have evolved an unparalleled mechanism to perfectly tackle the underwater adhesion problem. [15][16][17] The finding of universality of catechol chemistry for wet adhesion has provided a valuable biomimetic source to develop diverse adhesives for use in aqueous environments. However, several problems, such as the complexity of administration, release of harmful organic solvents, [18,19] long-term curing, [2] need for oxidant addition, [20,21] and low adhesion strength, [18,22] may hamper the actual applications of these bioinspired adhesives.…”
mentioning
confidence: 99%
“…The triethylamine salt was removed through repeated frozen and crystallized of solution, followed by acrylated adenine (Aa) was precipitated by diethyl ether solution. The chemical structure was confirmed by 1 H-NMR (400 MHz, DMSO-d 6 , δ ppm) and 13 Preparation of Adhesive Gels: 2 g acrylic acid, 2 g methoxyethyl acrylate, 0.2 g Aa, and 0.04 g KPS were added into solution consisting of DMSO (5 mL) and water (5 mL). The solution was continuously stirred until homogeneous and poured into a cylindrical Teflon reactor (50 mm diameter).…”
Section: Methodsmentioning
confidence: 99%
“…Yuk et al presented a chemical anchor strategy to fabricate a tough interface between hydrogels and nonporous solid substrate surfaces. [11] Moreover, underwater adhesion also achieved a prominent progress based on various nature-inspired strategies, including 3,4-dihydroxyphenyl-L-alanine (DOPA)-modified adhesives, [12,13] structure-inspired adhesives, [14][15][16] and biomimetic protein adhesives. [10] Gao et al demonstrated a photodetachable adhesion principle to achieve strong adhesion and easy on-demand detachment for various materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation